Dietary guidelines for the Asia Pacific Region: Report of the Asia Pacific academic consortium for public health workshop 2016 - Binns, Colin; Lee, M.; Kagawa, Masaharu; Low, W.; Liqian, Q.; Guldan, G.; Hokama, T.; Nanishi, K.; Oy, S.; Tang, L.; Zerfas, A. (Sage Publications, 2017)
© 2017 APJPH. Nutrition is a major determinant of health throughout all stages of life and together with smoking is the most important risk factor for morbidity and mortality in the Asia Pacific Region. The workshop participants examined Dietary Guidelines and Food Guides tha t are in use in our region, together with additional materials from the World Health Organization, UNICEF and the World Cancer Research Foundation. The resulting set of guidelines is meant as a reminder of the main issues to be covered in a general public health education program. It may also be of value in reminding public health practitioners, educators, administrators, and policy makers of current nutrition issues. It may additionally be useful as a checklist of the issues to be considered in public health programs and regulations. The main areas of nutrition that are included in the Guidelines are eating a variety of foods, including vegetables, fruits, whole grain cereals, and nuts. Choose fish, poultry, and meats grown in a sustainable way. Appropriate growth, including avoiding obesity, and physical activity are important. Breastfeeding is the basis of infant nutrition and nutrition of mothers is an important public health measure. Negative factors in the Asian diet include salt, refined sugar, alcohol and fats. The APACPH Dietary Guidelines will need to be kept under review and modified to meet regional differences in food supply. The Guidelines will be useful as a checklist of the issues to be considered in public health programs, addressing both acute and chronic diseases.